LEXICOLOGY AND ITS RELATIONSHIP WITH OTHER LINGUISTIC DISCIPLINES - Bakhtiyorova Raykhona Ikhtiyorovna; Bakhtiyorova Maftuna Bakhtiyorovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. It delves into the examination of words and their structures, emphasizing their roles in language systems. It discusses how lexicology, as a scientific discipline, contributes to our understanding of language in the current linguistic science. The exploration encompasses the analysis of lexical units, their meanings, and the evolving nature of language. The study aims to provide insights into the crucial role lexicology plays in unraveling the intricacies of language and communication within the framework of present day linguistics.